2023
DOI: 10.1177/17534666231167716
|View full text |Cite
|
Sign up to set email alerts
|

Antitussive efficacy of the current treatment protocol for refractory chronic cough: our real-world experience in a retrospective cohort study

Abstract: Background: The management of refractory chronic cough (RCC) is a great challenge. Neuromodulators have long been used for RCC with imperfect efficacy. Objectives: We summarized the outcomes of the current treatments used at our specialist cough clinic, which provides a guideline-led service and real-world experience for the future management of RCC. Design: This is a single-centre retrospective observational cohort study. Methods: Consecutive RCC patients (the first clinic visit between January 2016 and May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The decreased CaNO combined with cough relief also suggests the potential for CaNO to be used in predicting the response to anti-reflux treatment and being used as a treatment outcome indicator in real-world practice. Since relapse may occur upon withdrawal of treatment or reduction of dosage, 16 regular CaNO follow-ups may better guide the course of therapy. Currently, several MII-pH parameters such as SAP, AET, and mean nocturnal baseline impedance are used to predict GERC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased CaNO combined with cough relief also suggests the potential for CaNO to be used in predicting the response to anti-reflux treatment and being used as a treatment outcome indicator in real-world practice. Since relapse may occur upon withdrawal of treatment or reduction of dosage, 16 regular CaNO follow-ups may better guide the course of therapy. Currently, several MII-pH parameters such as SAP, AET, and mean nocturnal baseline impedance are used to predict GERC.…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive patients with GERC and non-GERC who visited our cough clinic between March 2021 and October 2022 were recruited into the study. A GERC diagnosis was considered when the following criteria were met: (I) the patient presented with a cough which had lasted for at least 2 months; (II) multichannel intraluminal impedance and pH monitoring (MII-pH) revealed abnormal gastroesophageal reflux: acid exposure time (AET) >6%, symptom association probability (SAP) ⩾ 95%, and reflux episodes >80 times in 24 h 13 ; and (III) cough responded to a stepwise anti-reflux treatment protocol, 14 16 available in Supplemental Table 1 . Patients with predominant abnormal acidic and non-acidic reflux were diagnosed with acid GERC and non-acid GERC, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These drugs may potentially induce hepatic and renal injuries (Kayode, Kayode, and Oridota 2021) About the use of neuromodulators, like gabapentin, for refractory chronic cough (RCC) management a study found that despite the efficacy of these agents, relapse was more common upon withdrawal or reduction of dosage. The study emphasized the dire need for developing novel medication for RCC management (Zhang et al 2023).…”
Section: Challenges With Conventional Treatmentmentioning
confidence: 99%